Pengaruh Insentif Promosi Jabatan dan Motivasi Terhadap Kinerja Karyawan Pada PT. Bintang Perkasa Indah Motor di Lueng Bata - Rike Nurhajjah (Gabungan Riset Edukasi dan Ekplorasi Teori (GREET), 2024)
The purpose of this study is to determine the effect of Incentives, Job Promotion and Motivation on Employee Performance at PT. Bintang Perkasa Indah Motor in Lueng Bata. The sample size of this study was 40 employees. Research data were collected through a list of questions/questionnaires and documentation studies. Hypothesis testing using multiple linear regression analysis, F test (simultaneous) and t test (partial) is intended to determine the effect of independent variables on the dependent variable at a 95% confidence level (α = 0.05). The objects in this study are Incentives, Job Promotion, Motivation and Employee Performance at PT. Bintang Perkasa Indah Motor in Lueng Bata. The results of the study show that in a simultaneous test between the variables Incentives, Job Promotion and Motivation affect employee performance at PT. Bintang Perkasa Indah Motor in Lueng Bata. Then partially, namely Job Promotion and Motivation affect employee performance at PT. Bintang Perkasa Indah Motor in Lueng Bata. While Incentives do not affect employee performance at PT. Bintang Perkasa Indah Motor in Lueng Bata